Legal Politics Legislative Law Number 13 of 2012 Concerning Privileges of the Special Region of Yogyakarta - Ariyanti Luhur Tri Setyarini; Benedictus Hestu Cipto Handoyo; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The 1945 Constitution has been amended 4 times. The results of the second amendment to the 1945 Constitution, specifically added the formulation of an article regarding special regions. This study aims to analyze the legal politics that underlies the legislative process of Law Number 13 of 2012 concerning Privileges of DIY, related to the problem of how the Special Constituendum of the Special Region of Yogyakarta in the Era of Constitutional Democracy. Legal politics is a legal policy that the government wants to or has implemented nationally. The research method uses a socio-legal research approach . The results of the study show that Indonesia in its regional autonomy concept adheres to asymmetric decentralization, namely by legally recognizing special and special autonomous regions constitutionally. The recognition of the Special Region of Yogyakarta is inseparable from philosophical, sociological and juridical factors. With the enactment of Law Number 13 of 2012 concerning Privileges of DIY, DIY has additional authority apart from the authority already regulated in the Law on Regional Government